Effectiveness of Planned Teaching Program on Knowledge Regarding Intimate Partner Violence among Final Year BSc Nursing Students of Selected Nursing Colleges, Mangaluru - Geetha B V; Bibi Augustin (RGUHS Journal of Nursing Sciences)
Background and Aim Violence among intimate partners is a major public health concern resulting in violation of human rights. Efficacy of a planned education program on knowledge regarding intimate partner violence was investigated in this study. The studyrsquos objective was to improve the fourth year B.Sc. nursing studentsrsquo understanding of intimate partner violence.Methods Two-group pre-test and post-test study design using a quasi-experimental approach was followed. Eighty fourth year BSc nursing students from select Mangaluru nursing colleges were included in the study using a convenient sampling technique. Statistical analysis was done using Chi-Square paired and unpaired ldquotrdquo tests Fisherrsquos exact test.Results The mean pretest and post-test scores of the experiment group were 14.55 plusmn 3.637 and 18.73 plusmn 4.089 respectively with a 28.69 improvement which was highly significant P 0.001. Overall difference in the knowledge between experimental and control groups was found to be significant P 0.007. No significant association was found between socio demographic factors and the pretest levels of knowledge in both the groups except for the source of information regarding intimate partner violence chi2 7.025 P 0.008 in experiment group.Conclusion The study concluded that in comparison to their prior knowledge fourth year BSc nursing students had a significantly higher understanding of intimate partner abuse after implementation of teaching programme. The intended teaching program can bring significant improvement among final year BSc Nursing students and suggested that further evidence-based research should be conducted to raise awareness knowledge regarding intimate partner violence.